Recent Developments in Microbe–Plant-Based Bioremediation for Tackling Heavy Metal-Polluted Soils - Saha, Lala; Tiwari, Jaya; Bauddh, Kuldeep; Ma, Ying (Frontiers in Microbiology, 2021)
Soil contamination with heavy metals (HMs) is a serious concern for the developing world due to its non-biodegradability and significant potential to damage the ecosystem and associated services. Rapid industrialization and activities such as mining, manufacturing, and construction are generating a huge quantity of toxic waste which causes environmental hazards. There are various traditional physicochemical techniques such as electro remediation, immobilization, stabilization, and chemical reduction to clean the contaminants from the soil. However, these methods require high energy, trained manpower and hazardous chemicals make these techniques costly and non-environment friendly. Bioremediation, which includes microorganism-based, plant-based, microorganism-plant associated, and other innovative methods, is employed to restore the contaminated soils. This review covers some new aspects and dimensions of bioremediation of heavy metal polluted soils. The bioremediation potential of bacteria and fungi individually and in association with plants has been reviewed and critically examined. It is reported that microbes such as Pseudomonas spp., Bacillus spp., and Aspergillus spp., have high metal tolerance, and bioremediation potential up to 98% both individually and when associated with plants such as Trifolium repens, Helianthus annuus, and Vallisneria denseserrulata. The mechanism of microbe’s detoxification of metals depends upon various aspects which include the internal structure, cell surface properties of microorganisms and the surrounding environmental conditions has been covered. Further, factors affecting the bioremediation efficiency and their possible solution, along with challenges and future prospects also discussed.